2022
DOI: 10.1007/s11259-022-09975-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplets and perilipins in canine osteosarcoma. Investigations on tumor tissue, 2D and 3D cell culture models

Abstract: Lipid droplets were identified as important players in biological processes of various tumor types. With emphasis on lipid droplet-coating proteins (perilipins, PLINs), this study intended to shed light on the presence and formation of lipid droplets in canine osteosarcoma. For this purpose, canine osteosarcoma tissue samples (n = 11) were analyzed via immunohistochemistry and electron microscopy for lipid droplets and lipid droplet-coating proteins (PLINs). Additionally, we used the canine osteosarcoma cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…Cells were cultured for at least 20 passages before entering the characterization process, except for COS4074 cells, where the characterization started at passage 17, representing 5–6 month of continuous COS4074 cell cultivation. The isolation of COS4288 cells was carried out in a similar manner, as recently described in [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cells were cultured for at least 20 passages before entering the characterization process, except for COS4074 cells, where the characterization started at passage 17, representing 5–6 month of continuous COS4074 cell cultivation. The isolation of COS4288 cells was carried out in a similar manner, as recently described in [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The soft agar colony formation assay was performed as described [ 26 ]. Colony formation was evaluated after 21 days for COS3600B, COS4288, and D-17 and after 56 days for COS3600 and COS4074 cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Canine cancer cell have been cultured most commonly as 2D cultures obtained from several types of neoplasms, including soft and hard tissue sarcoma [11][12][13][14] and different histotypes of carcinoma [15][16][17] to demonstrate feasibility, obtain abundant neoplastic cell material for genetic studies and for therapy e cacy assessment. For osteosarcoma, lymphoma [18,19] and mammary carcinoma, [17] 3D cultures systems have been recently used to study speci c target therapies and demonstrate the importance of the tumor speci c stromal microenvironment. These studies have demonstrated the better performances and the essential role of 3D culture systems for the understanding of treatment response and the emergence of chemo-resistant clones.…”
Section: Introductionmentioning
confidence: 99%